2009
DOI: 10.1037/a0015362
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in middle school: A meta-analytic assessment of the strategies that promote achievement.

Abstract: Early adolescence is often marked by changes in school context, family relationships, and developmental processes. In the context of these changes, academic performance often declines, while at the same time the long-term implications of academic performance increase. In promoting achievement across elementary and secondary school levels, the significant role of families, familyschool relations, and parental involvement in education has been highlighted. Although there is a growing body of literature focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

55
1,253
11
133

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,452 publications
(1,452 citation statements)
references
References 103 publications
55
1,253
11
133
Order By: Relevance
“…That is, research has shown that homework help may have not only positive but also detrimental effects on students' academic development (H. Cooper, Lindsay, & Nye, 2000;Desimone, 1999;Pomerantz, Wang, & Ng, 2005;Xu, 2004). In line with these findings, Hill and Tyson (2009) reported in their meta-analysis that homework help was the only type of involvement that was not consistently related to academic achievement. Similarly, in a metaanalysis by Patall, Cooper, and Robinson (2008), focusing only on parental homework involvement, the authors concluded that it has "at best a slightly positive overall impact on achievement" (p. 1062).…”
supporting
confidence: 68%
See 3 more Smart Citations
“…That is, research has shown that homework help may have not only positive but also detrimental effects on students' academic development (H. Cooper, Lindsay, & Nye, 2000;Desimone, 1999;Pomerantz, Wang, & Ng, 2005;Xu, 2004). In line with these findings, Hill and Tyson (2009) reported in their meta-analysis that homework help was the only type of involvement that was not consistently related to academic achievement. Similarly, in a metaanalysis by Patall, Cooper, and Robinson (2008), focusing only on parental homework involvement, the authors concluded that it has "at best a slightly positive overall impact on achievement" (p. 1062).…”
supporting
confidence: 68%
“…Although a large number of authors have criticized the heterogeneous conceptualization and poor measurement of parental involvement (e.g., Fan & Chen, 2001;Gerber & Wild, 2009;Harris & Goodall, 2008;Hill & Tyson, 2009;Jeynes, 2003), the field still has not overcome some of its conceptual and methodological limitations. With the present study, we wanted to advance research on parental involvement by showing how the results differ depending on the measures and control variables used.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…One of the explanations for the mixed results is the complexity of the parental involvement concept (Fan and Chen 2001;Hill and Tyson 2009;Castro et al 2015). Both the meta-studies and our literature review indicated that measurement of parental involvement dimensions differed considerably among studies.…”
Section: The Relation Between Parental Involvement and Student Attainmentioning
confidence: 95%